2013
DOI: 10.1007/s40272-013-0043-3
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Allergic Rhinitis and Asthma: Can the March be Halted?

Abstract: The strong epidemiologic and pathophysiologic link between allergic rhinitis (AR) and asthma has led to the concept of 'united airways disease' or 'respiratory allergy', implying that allergy, in its widest sense, underlies this clinical syndrome. Progression from AR to asthma is frequent and part of the 'atopic march'. Since pediatric immune responses are more adaptable and therefore may be more amenable to treatment, interventions at early childhood are characterized by a higher chance to affect the natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 108 publications
3
20
0
Order By: Relevance
“…In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15]. More than one-third of patients with AR have asthma [2]; AR frequently precedes the development of asthma and has been proposed as an independent risk factor for it [16].…”
Section: Abstract: 5-grass-pollen Tablet • Allergic Rhinitis • Allergsupporting
confidence: 71%
See 1 more Smart Citation
“…In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15]. More than one-third of patients with AR have asthma [2]; AR frequently precedes the development of asthma and has been proposed as an independent risk factor for it [16].…”
Section: Abstract: 5-grass-pollen Tablet • Allergic Rhinitis • Allergsupporting
confidence: 71%
“…In a recent study, allergic conjunctivitis was identified in 53.5% of patients with AR, a finding comparable to those from other studies [15]. More than one-third of patients with AR have asthma [2]; AR frequently precedes the development of asthma and has been proposed as an independent risk factor for it [16].Both US and EU guidance recommend that management of AR combines patient education with specific allergen avoidance, symptomatic pharmacotherapy and allergen-specific immunotherapy (AIT) [1,2,4]. It is typically not possible to eliminate exposure to pollen; therefore, drug treatment is often necessary to provide symptomatic relief.…”
supporting
confidence: 71%
“…It is also possible that the relationship between AR and asthma could be, at least in part, causal. 19,34,[45][46][47] This idea is supported by findings of significantly impaired lung function in children with moderate-severe persistent rhinitis, compared to mild intermittent rhinitis, in children without overt asthma symptoms, which was independent of atopic status. 30 Studies showing that provocation of nasal mucosa with allergen in patients with AR caused pulmonary symptoms and decreased airway function, and similarly segmental bronchial provocation triggered nasal inflammation, support the unified airway concept.…”
Section: Allergic Rhinitismentioning
confidence: 75%
“…30 Studies showing that provocation of nasal mucosa with allergen in patients with AR caused pulmonary symptoms and decreased airway function, and similarly segmental bronchial provocation triggered nasal inflammation, support the unified airway concept. 44,46 These mechanisms may underlie the relationship between AR and STRA. 19,34,[45][46][47] This idea is supported by findings of significantly impaired lung function in children with moderate-severe persistent rhinitis, compared to mild intermittent rhinitis, in children without overt asthma symptoms, which was independent of atopic status.…”
Section: Allergic Rhinitismentioning
confidence: 99%
“…The incidence of cedar pollen allergy (a seasonal type of AR) has also been increasing, and its prevalence in 5-9-year-old children was demonstrated to be 13.7%, according to a survey performed in 2008 (5). As both diseases affect the airways and exacerbation of nasal symptoms influences asthma symptoms, these two diseases are increasingly viewed from the perspective of the 'one airway, one disease' paradigm (6). Pranlukast dry syrup is an LTRA that is used as a monotherapy for bronchial asthma or AR (7)(8)(9)(10); however, its use in children with both diseases has not been examined.…”
Section: Introductionmentioning
confidence: 99%